RENCANA STRATEGIS PENINGKATAN KINERJA POLIKLINIK EKSEKUTIF RUMAH SAKIT X TAHUN 2024 -2027: PENDEKATAN BALANCED SCORECARD - Manik, Irfan Rohot Uli; Bachtiar, Adang (UI Scholars Hub, 2024)
Hospital X is a private hospital that has executive polyclinic services. Medical record data shows that in the last four years, the number of visits from the executive polyclinic unit has never reached the target set. This research is to prepare the strategic plan for improving the executive polyclinic of Hospital X's performance for 2024-2027. The types of data in this research are primary data and secondary data. Primary data is qualitative data from in-depth interviews, Consensus Decision Making Group (CDMG) with informants, and direct observation. Secondary data consists of quantitative data and qualitative data. Strategy implementation will be described as Key Performance Indicators (KPI) using the Balanced Scorecard (BSC) approach. The Matching Stage results in the IE matrix show the position of the hospital in cell 1 in the IE matrix, namely grow and build. The QSPM results combined with existing theory in determining priority strategies produce the following strategy sequence: optimizing promotion, optimizing facilities and facilities, optimizing products and services, optimizing technology, optimizing human resources, and optimizing service excellence. The conclusion is that the strategic plan, made complete with indicators according to the BSC and targets, will be able to serve as a guide for Hospital X in realizing executive polyclinic services as superior services.